PERANAN ORENTASI K3L/SAFETY INDUCTION PADA PEKERJA DI PROYEK KONSTRUKSI DALAM RANGKA MENCEGAH KECELAKAAN KERJA - Subaidi Subaidi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2022)
PT Prambanan Dwipaka continues to invest a lot of time and capital into its workforce, believing that employees are the Company's greatest asset. Intensive job training, safety induction programs, introduction to occupational safety and health, and additional facilities contribute to employee welfare, which in turn translates into good productivity and quality control. The construction sector has a strategic role in driving Indonesia's development. PT. Prambanan Dwipaka has been trusted by the Government of Indonesia to work on major projects, contributing to national growth and infrastructure. PT Prambanan Dwipaka is also known for the quality of its products, both in the government and private sectors. PT Prambanan Dwipaka is committed to creating a work environment that is safe and free from work accidents and environmental pollution, for this reason work safety is a top priority for the company.